A high-brightness black glass microbead license plate grade reflective film and preparation method thereof

By using a high-brightness black glass microbead type license plate-grade reflective film in the black license plate film, the thickness and composition of each layer are optimized, and the problem of low reflective brightness of the existing black license plate film is solved, achieving higher reflective brightness and better diversified applications.

CN112051632BActive Publication Date: 2025-04-11ZHEJIANG LONGYOU DAOMING OPTICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011063939.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-11
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The existing black license plate film has low reflective brightness, which limits the diversified application of black license plates.

Method used

A high-brightness black glass micro-bead type license plate-grade reflective film is adopted. The structure includes a transparent composite surface layer, a black bead planting layer, a focus layer, an aluminum-plated layer, a glue back layer and a release layer in turn from bottom to top. By optimizing the thickness and composition of each layer, the regression reflection effect of light is enhanced.

Benefits of technology

The reflective brightness is significantly improved, and the defect of residual black color layer between the glass microbeads and the surface layer in the prior art is overcome, which enhances the reflective brightness performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112051632B_ABST
    Figure CN112051632B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-brightness black glass bead type license plate grade reflective film, which includes a transparent composite surface layer, a black bead planting layer, a focusing layer, an aluminum plating layer, an adhesive layer, and a release layer from bottom to top. The black bead planting layer includes a black color layer and glass beads, and the glass beads are embedded in the black color layer. The transparent composite surface layer includes a first surface layer and a second surface layer. The thickness of the second surface layer is 20-30% of the particle size of the glass beads, and the sum of the thickness of the black color layer and the second surface layer is 60-80% of the particle size of the glass beads. The glass beads sink into the second surface layer, and the bottom of the glass beads contacts the first surface layer. The glass beads of the present invention sink into the second surface layer and contact the first surface layer, so that the black color layer does not affect the propagation of light to the glass beads, overcomes the defect of the residual black color layer between the glass beads and the surface layer in the prior art, and enhances the reflective brightness performance of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of reflective films, and in particular to a high-brightness black glass microbead license plate-grade reflective film and a preparation method thereof. Background Art

[0002] Nowadays, different countries have different preferences for license plate appearance, color, and materials. Black license plates have always been popular among people. Black is darker and more noticeable, so black reflective film is increasingly used in the field of license plates. However, the black color layer of the black license plate film is on the surface layer, and it is difficult for light to be transmitted to the microbeads, so the reflective brightness of the black license plate film is low, which limits the diversified application of black license plates. Summary of the invention

[0003] Aiming at the defect of low reflective brightness of black license plate film in the prior art, the present invention provides a new high-brightness black glass micro-bead license plate grade reflective film and a preparation method thereof.

[0004] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0005] A high-brightness black glass bead license plate-grade reflective film comprises, from bottom to top, a transparent composite surface layer, a black bead planting layer, a focusing layer, an aluminum-plated layer, a back adhesive layer, and a release layer, wherein the release layer is one of release paper, release PET or CPP, the back adhesive layer is a thermoplastic acrylic pressure-sensitive adhesive, the focusing layer is one of polyester resin, polyurethane resin, and acrylic resin, the black bead planting layer comprises a black color layer and glass beads, the glass beads are embedded in the black color layer, the transparent composite surface layer comprises a first surface layer and a second surface layer, the thickness of the first surface layer is 35 to 50 μm, the thickness of the second surface layer is 20 to 30% of the particle size of the glass beads, the sum of the thickness of the black color layer and the second surface layer is 60 to 80% of the particle size of the glass beads, the second surface layer is a thermoplastic surface layer, the glass beads sink into the second surface layer, and the bottom of the glass beads contacts the first surface layer.

[0006] The transparent composite surface layer of the present invention is a colorless transparent resin film, the focusing layer can make the light have a better retro-reflective effect when passing through the black bead layer, thereby obtaining a higher reflective brightness, the aluminum-plated layer can further improve the reflective effect of the present invention, the back glue layer is used for bonding with the carrier, and the release layer has the function of protecting the back glue layer.

[0007] The second surface layer of the present invention is a thermoplastic surface layer, and the glass beads sink into the second surface layer and contact the first surface layer, so that the black color layer does not affect the transmission of light to the glass beads, thereby enhancing the reflective brightness of the present invention. The present invention overcomes the defect of the black color layer remaining between the glass beads and the surface layer in the prior art, thereby significantly enhancing the reflective brightness performance of the present invention.

[0008] Preferably, the method for preparing the high-brightness black glass bead type license plate grade reflective film described above comprises the following steps:

[0009] Q1: Take PET without corona treatment as the coating substrate, the PET has a temperature resistance of 180-220°C, a heat shrinkage rate of less than 1.5%, and a thickness of 50-100 μm;

[0010] Q2: Resin A, trimer isocyanate A and methyl cellulose are mixed, wherein the weight ratio of the resin A, trimer isocyanate A and methyl cellulose is 100:0.5-15:3-8, and the mixture is stirred for 20-30 minutes at a speed of 800-1000 rpm. After stirring, the mixture is coated on PET, and then placed in an oven at 75-155°C and dried for 5-8 minutes to obtain the first surface layer;

[0011] Q3: Mix resin B, chlorovinyl acetate resin and trimer isocyanate B, wherein the weight ratio of resin B, chlorovinyl acetate resin and trimer isocyanate B is 100:10-15:0.5-1.5, stir thoroughly for 20-30 minutes, and the stirring speed is 800-1000 rpm. After stirring, apply it on the first surface layer, and then place it in an oven at 75-155°C and dry it for 5-8 minutes to obtain the second surface layer;

[0012] Q4: Mix black ink and solvent, wherein the black ink contains grinding resin, dispersant, and carbon black, and the weight ratio of the grinding resin, dispersant, carbon black to the solvent is 100:5-10:30-40:40-50. Stir thoroughly for 3-5 minutes, and filter with 200-mesh cloth after stirring to obtain black pigment;

[0013] Q5: Take resin C, mix it with the black pigment, stir it for 6 to 8 minutes, then add isocyanate and organotin catalyst, wherein the weight ratio of resin C, black pigment, isocyanate and organotin catalyst is 100:4 to 8:0.5 to 15:0.01 to 0.015, continue stirring for 20 to 30 minutes, the stirring speed is 800 to 1000 rpm, after stirring, apply it on the second surface layer, and then place it in an oven at 90 to 130°C and dry it for 2 to 3 minutes to obtain a black color layer that is not completely dried;

[0014] Q6: Using a bead planting device, glass micro beads are evenly and densely arranged on the black color layer, and then placed in an oven at 110-150° C. for drying for 3-4 minutes to obtain a black bead planting layer;

[0015] Q7: Take resin D, apply it on the black bead layer, and then place it in an oven at 100-155°C for 8-10 minutes to obtain a focusing layer;

[0016] Q8: Using vacuum aluminum plating equipment, the vacuum degree is set to 133Pa, the winding speed is set to 100-150m / min, and the aluminum feeding speed is set to 0.15-0.35m / min. After the vacuum aluminum plating is completed, an aluminum plating layer is formed on the surface of the focusing layer;

[0017] Q9: Take the release layer, apply the thermoplastic acrylic pressure-sensitive adhesive on the release layer, and then place it in an oven at 90-120°C for 3-5 minutes to obtain a back adhesive layer;

[0018] Q10: Use a composite device and set the composite pressure to 0.4-0.6 MPa to composite the back adhesive layer and the aluminum-plated layer, then peel off the PET and the first surface layer, and after rolling up, obtain a high-brightness black glass bead license plate grade reflective film.

[0019] In step Q1, the use of PET with good temperature resistance can ensure that it is not easy to deform and shrink during the coating process.

[0020] In step Q2, resin A, trimer isocyanate A, and methyl cellulose are mixed and coated, and dried at 75-155° C. to obtain a first surface layer with a smooth surface and no obvious bubbles. Resin A, trimer isocyanate A, and methyl cellulose are mixed, and the three can be fully cross-linked and cured during the high-temperature drying process, so that the first surface layer has better tensile strength, breaking strength, and solvent resistance, and also makes the peelability between the first surface layer and PET better.

[0021] In step Q3, the three resins of resin B, chloroacetic acid resin, and trimer isocyanate B are mixed and stirred until completely dissolved, which can avoid the formation of gel in the subsequent reaction process. The second surface layer obtained by mixing the above-mentioned resin B, chloroacetic acid resin, and trimer isocyanate B will soften at high temperatures, which can make the glass microbeads continue to settle into the second surface layer after implantation due to the gravity of the glass microbeads themselves and the softening effect of the second surface layer until they contact the first surface layer. In addition, the second surface layer obtained by using the above-mentioned components has better adhesion to the first surface layer.

[0022] In step Q4, the black ink and the solvent are mixed, stirred, and filtered to fully disperse the black ink.

[0023] In step Q5, the black pigment and resin C are first mixed and stirred, and then isocyanate and organotin catalyst are added, so that the black pigment can be completely dispersed in the resin C, with better compatibility, and the uniformity of the coating color is ensured. Drying under an environment of 90 to 130° C. allows the black color layer to reach a surface dry state, which is conducive to the subsequent implantation and sedimentation of glass microbeads. The formulation of resin C, isocyanate and organotin catalyst can not only accelerate the crosslinking reaction, but also increase the adhesion performance of the glass microbeads and the black color layer, and improve the tensile strength performance of the present invention.

[0024] In step Q6, glass micro beads are implanted into the black color layer and fully dried to completely evaporate the solvent in the black color layer, thereby obtaining a uniform and dense black implanted bead layer.

[0025] In step Q7, the resin D is dried in an oven at 100-155° C. to allow the components of the resin D to undergo sufficient cross-linking and curing reactions.

[0026] In step Q8, vacuum aluminum plating is performed in a vacuum environment of 133 Pa, and an aluminum plating layer evenly covering the focusing layer can be obtained after the aluminum wire is vaporized.

[0027] In step Q9, drying is performed at 90-120° C. to fully cure the thermoplastic acrylic pressure-sensitive adhesive.

[0028] In step Q10, the adhesive layer and the aluminum-plated layer are fully pressed together under a composite pressure environment of 0.4-0.6 MPa, which is conducive to the discharge of air and is not easy to generate bubbles.

[0029] Preferably, in the above-mentioned high-brightness black glass bead license plate-grade reflective film, the particle size of the glass beads is 45 to 80 μm, and the refractive index is 2.1 to 2.3.

[0030] The glass microspheres with high refractive index are selected to make the present invention have better retro-reflective effect. The light passing through the glass microspheres has higher reflective brightness after being reflected by the aluminum-plated layer.

[0031] Preferably, in the above-mentioned method for preparing a high-brightness black glass bead type license plate grade reflective film, in step Q2, the resin A comprises one or more of thermoplastic polyester resin, polyurethane resin, and acrylic resin.

[0032] The resin A is used to make the first surface layer finally obtained have better peelability.

[0033] Preferably, in the above-mentioned method for preparing a high-brightness black glass microbead license plate grade reflective film, in step Q3, the resin B comprises one or more of a thermoplastic polyester resin, a polyurethane resin, and an acrylic resin, the thermoplastic polyester resin has a glass transition temperature of 30-50°C, a molecular weight of 15000-25000Mw, and a hydroxyl value of 6mgKOHg-10mgKOHg, the polyurethane resin has a Shore hardness of 75-80, a melting temperature of 120-130°C, the acrylic resin has a molecular weight of 5000-6000Mw, and a glass transition temperature of 65-70°C, the chloroacetic acid resin is a ternary chloroacetic acid resin, the chloroacetic acid resin has a vinyl acetate content of 10-15%, and a hydroxyl value of 50mgKOH / g-60mgKOH / g.

[0034] The use of the resin B can improve the adhesion strength between the second surface layer and the first surface layer finally obtained.

[0035] Preferably, in the above-described method for preparing a high-brightness black glass microbead license plate-grade reflective film, in step Q4, the solid content of the black ink is 30-40%, the color content is 15-20%, the grinding resin comprises one or more of ternary chloroacetic resin, acrylic resin, polyester resin, and vinyl resin, the hydroxyl value of the grinding resin is 70mgKOH / g-80mgKOH / g, the dispersant is an anionic carboxylic acid ammonium salt dispersant, the carbon black is ordinary pigment tank carbon black, the blackness My value of the carbon black is 200-300, the oil absorption is 250g / 100g-350g / 100g, and the primary particle size is 20nm-30nm.

[0036] The selected carbon black with high chroma and small particle size can increase the color concentration of black ink and make the black ink have better dispersion performance in resin C. The selected anionic carboxylic acid ammonium salt dispersant can avoid flocculation, precipitation and aggregation of black ink, thereby making the compatibility and glossiness of black ink better.

[0037] Preferably, in the above-mentioned method for preparing a high-brightness black glass bead type license plate grade reflective film, in step Q5, the resin C is one of polyester resin, polyurethane resin and acrylic resin.

[0038] Resin C has better compatibility, making the color of the final black color layer more uniform.

[0039] Preferably, in the above-mentioned high-brightness black glass bead type license plate grade reflective film, in step Q7, the resin D is one of polyester resin, polyurethane resin and acrylic resin.

[0040] The focusing layer is selected from one of polyester resin, polyurethane resin and acrylic resin, so that the strength and elongation of the focusing layer are better, so that the present invention is not easy to deform and crack during the processing deformation process.

[0041] Preferably, in the above-mentioned high-brightness black glass bead type license plate grade reflective film, in step Q4, the solvent is one of a lipid solvent, a benzene solvent, and a ketone solvent.

[0042] Using one of lipid solvents, benzene solvents and ketone solvents as the solvent of the present invention enables the present invention to have a better volatilization trapezoidal temperature, so that the black ink not only has better compatibility, but also improves the dispersion uniformity of the black ink in the resin C. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the structure of the high-brightness black glass bead type license plate grade reflective film of the present invention. DETAILED DESCRIPTION

[0044] The following is combined with Figure 1 The present invention is further described in detail with specific embodiments, but they are not intended to limit the present invention:

[0045] Example 1

[0046] A high-brightness black glass bead license plate grade reflective film, which includes, from bottom to top, a transparent composite surface layer 1, a black bead layer 2, a focusing layer 3, an aluminum-plated layer 4, a back adhesive layer 5, and a release layer 6, wherein the release layer 6 is one of release paper, release PET or CPP, the back adhesive layer 5 is a thermoplastic acrylic pressure-sensitive adhesive, the focusing layer 3 is one of polyester resin, polyurethane resin, and acrylic resin, the black bead layer 2 includes a black color layer 21 and glass beads 22, and the glass beads 22 are embedded in the black The color layer 21, the transparent composite surface layer 1 includes a first surface layer 11 and a second surface layer 12, the thickness of the first surface layer 11 is 35μm, the thickness of the second surface layer 12 is 20% of the particle size of the glass beads 22, the sum of the thickness of the black color layer 21 and the second surface layer 12 is 60% of the particle size of the glass beads 22, the second surface layer 12 is a thermoplastic surface layer, the glass beads 22 sink into the second surface layer 12, and the bottom of the glass beads 22 contacts the first surface layer 11.

[0047] As a preference, the method comprises the following steps:

[0048] Q1: Take PET without corona treatment as the coating substrate, the PET has a temperature resistance of 180°C, a heat shrinkage rate of less than 1.5%, and a thickness of 50 μm;

[0049] Q2: Resin A, trimer isocyanate A and methyl cellulose are mixed, wherein the weight ratio of the resin A, trimer isocyanate A and methyl cellulose is 100:0.5:3, and the mixture is stirred for 20 minutes at a speed of 800 rpm. After stirring, the mixture is coated on PET, and then placed in an oven at 75°C and dried for 5 minutes to obtain the first surface layer 11;

[0050] Q3: Mix resin B, chlorovinyl acetate resin and trimer isocyanate B, wherein the weight ratio of resin B, chlorovinyl acetate resin and trimer isocyanate B is 100:10:0.5, stir thoroughly for 20 minutes at a stirring speed of 800 rpm, apply on the first surface layer 11 after stirring, and then place in an oven at 75°C and dry for 5 minutes to obtain the second surface layer 12;

[0051] Q4: Mix black ink and solvent, wherein the black ink contains grinding resin, dispersant, and carbon black, and the weight ratio of the grinding resin, dispersant, carbon black to the solvent is 100:5:30:40. Stir thoroughly for 3 minutes, and filter with a 200-mesh cloth after stirring to obtain a black pigment;

[0052] Q5: Take resin C, mix it with the black pigment, stir it for 6 minutes, then add isocyanate and organotin catalyst, wherein the weight ratio of resin C, black pigment, isocyanate and organotin catalyst is 100:4:0.5:0.01, continue stirring for 20 minutes, the stirring speed is 800 rpm, after stirring, apply it on the second surface layer 12, and then place it in a 90°C oven and dry it for 2 minutes to obtain an incompletely dried black color layer 21;

[0053] Q6: Using a bead planting device, glass micro beads 22 are evenly and densely arranged on the black color layer 21, and then placed in an oven at 110°C for drying for 3 minutes to obtain a black bead planting layer 2;

[0054] Q7: Take resin D, apply it on the black bead layer 2, and then place it in an oven at 100°C and dry it for 8 minutes to obtain a focusing layer 3;

[0055] Q8: Using vacuum aluminum plating equipment, the vacuum degree is set to 133 Pa, the winding speed is set to 100 m / min, and the aluminum feeding speed is set to 0.15 m / min. After the vacuum aluminum plating is completed, an aluminum plating layer 4 is formed on the surface of the focusing layer 3;

[0056] Q9: Take the release layer 6, apply the thermoplastic acrylic pressure-sensitive adhesive on the release layer 6, and then place it in an oven at 90° C. and dry it for 3 minutes to obtain the back adhesive layer 5;

[0057] Q10: Use a composite device and set the composite pressure to 0.4 MPa to composite the adhesive layer 5 and the aluminum-plated layer 4, then peel off the PET and the first surface layer 11, and after rolling up, obtain a high-brightness black glass bead license plate grade reflective film.

[0058] Preferably, the glass microbeads 22 have a particle size of 45 μm and a refractive index of 2.1.

[0059] Preferably, in step Q2, the resin A comprises one or more of thermoplastic polyester resin, polyurethane resin and acrylic resin.

[0060] Preferably, in step Q3, the resin B comprises one or more of a thermoplastic polyester resin, a polyurethane resin, and an acrylic resin, the thermoplastic polyester resin having a glass transition temperature of 30°C, a molecular weight of 15000Mw, and a hydroxyl value of 6mgKOHg, the polyurethane resin having a Shore hardness of 75, a melting point of 120°C, the acrylic resin having a molecular weight of 5000Mw, and a glass transition temperature of 65°C, and the chloroacetic acid resin is a ternary chloroacetic acid resin, the chloroacetic acid resin having a vinyl acetate content of 10% and a hydroxyl value of 50mgKOH / g.

[0061] Preferably, in step Q4, the solid content of the black ink is 30%, the color content is 15%, the grinding resin comprises one or more of ternary chloroacetic resin, acrylic resin, polyester resin, and vinyl resin, the hydroxyl value of the grinding resin is 70 mgKOH / g, the dispersant is an anionic carboxylic acid ammonium salt dispersant, the carbon black is ordinary pigment tank carbon black, the blackness My value of the carbon black is 200, the oil absorption is 250g / 100g, and the primary particle size is 20nm.

[0062] Preferably, in step Q5, the resin C is one of polyester resin, polyurethane resin and acrylic resin.

[0063] Preferably, in step Q7, the resin D is one of polyester resin, polyurethane resin and acrylic resin.

[0064] Preferably, in step Q4, the solvent is one of a lipid solvent, a benzene solvent, and a ketone solvent.

[0065] Example 2

[0066] A high-brightness black glass bead license plate grade reflective film, which includes, from bottom to top, a transparent composite surface layer 1, a black bead layer 2, a focusing layer 3, an aluminum-plated layer 4, a back adhesive layer 5, and a release layer 6, wherein the release layer 6 is one of release paper, release PET or CPP, the back adhesive layer 5 is a thermoplastic acrylic pressure-sensitive adhesive, the focusing layer 3 is one of polyester resin, polyurethane resin, and acrylic resin, the black bead layer 2 includes a black color layer 21 and glass beads 22, and the glass beads 22 are embedded in the black The color layer 21, the transparent composite surface layer 1 includes a first surface layer 11 and a second surface layer 12, the thickness of the first surface layer 11 is 50μm, the thickness of the second surface layer 12 is 30% of the particle size of the glass beads 22, the sum of the thickness of the black color layer 21 and the second surface layer 12 is 80% of the particle size of the glass beads 22, the second surface layer 12 is a thermoplastic surface layer, the glass beads 22 sink into the second surface layer 12, and the bottom of the glass beads 22 contacts the first surface layer 11.

[0067] As a preference, the method comprises the following steps:

[0068] Q1: Take PET without corona treatment as the coating substrate, the PET has a temperature resistance of 220°C, a heat shrinkage rate of less than 1.5%, and a thickness of 100 μm;

[0069] Q2: Resin A, trimer isocyanate A and methyl cellulose are mixed, wherein the weight ratio of the resin A, trimer isocyanate A and methyl cellulose is 100:15:8, and the mixture is stirred for 30 minutes at a speed of 1000 rpm. After stirring, the mixture is coated on PET, and then placed in an oven at 155°C and dried for 8 minutes to obtain the first surface layer 11;

[0070] Q3: Mix resin B, chlorovinyl acetate resin and trimer isocyanate B, wherein the weight ratio of resin B, chlorovinyl acetate resin and trimer isocyanate B is 100:15:1.5, stir thoroughly for 30 minutes at a stirring speed of 1000 rpm, apply on the first surface layer 11 after stirring, and then place in an oven at 155°C and dry for 8 minutes to obtain the second surface layer 12;

[0071] Q4: Mix black ink and solvent, wherein the black ink contains grinding resin, dispersant, and carbon black, and the weight ratio of the grinding resin, dispersant, carbon black to the solvent is 100:10:40:50. Stir well for 5 minutes, and filter with 200-mesh cloth after stirring to obtain black pigment;

[0072] Q5: Take resin C, mix it with the black pigment, stir it for 8 minutes, then add isocyanate and organotin catalyst, wherein the weight ratio of resin C, black pigment, isocyanate and organotin catalyst is 100:8:15:0.015, continue stirring for 30 minutes, the stirring speed is 1000 rpm, after stirring, apply it on the second surface layer 12, and then place it in an oven at 130°C and dry it for 3 minutes to obtain an incompletely dried black color layer 21;

[0073] Q6: Using a bead planting device, glass micro beads 22 are evenly and densely arranged on the black color layer 21, and then placed in an oven at 150° C. for drying for 4 minutes to obtain a black bead planting layer 2;

[0074] Q7: Take resin D, apply it on the black bead layer 2, and then place it in an oven at 155°C and dry it for 10 minutes to obtain a focusing layer 3;

[0075] Q8: Using vacuum aluminum plating equipment, the vacuum degree is set to 133 Pa, the winding speed is set to 150 m / min, and the aluminum feeding speed is set to 0.35 m / min. After the vacuum aluminum plating is completed, an aluminum plating layer 4 is formed on the surface of the focusing layer 3;

[0076] Q9: Take the release layer 6, apply the thermoplastic acrylic pressure-sensitive adhesive on the release layer 6, and then place it in an oven at 120° C. and dry it for 5 minutes to obtain the back adhesive layer 5;

[0077] Q10: Use a composite device and set the composite pressure to 0.6 MPa to composite the back adhesive layer 5 and the aluminum-plated layer 4, then peel off the PET and the first surface layer 11, and after rolling up, obtain a high-brightness black glass bead license plate grade reflective film.

[0078] Preferably, the glass beads 22 have a particle size of 80 μm and a refractive index of 2.3.

[0079] Preferably, in step Q2, the resin A comprises one or more of thermoplastic polyester resin, polyurethane resin and acrylic resin.

[0080] Preferably, in step Q3, the resin B comprises one or more of a thermoplastic polyester resin, a polyurethane resin, and an acrylic resin, wherein the thermoplastic polyester resin has a glass transition temperature of 50°C, a molecular weight of 25000Mw, and a hydroxyl value of 10mgKOHg, the polyurethane resin has a Shore hardness of 80, a melting point of 130°C, the acrylic resin has a molecular weight of 6000Mw, and a glass transition temperature of 70°C, and the chloroacetic acid resin is a ternary chloroacetic acid resin, wherein the chloroacetic acid resin has a vinyl acetate content of 15% and a hydroxyl value of 60mgKOH / g.

[0081] Preferably, in step Q4, the solid content of the black ink is 40%, the color content is 20%, the grinding resin comprises one or more of ternary chloroacetic resin, acrylic resin, polyester resin, and vinyl resin, the hydroxyl value of the grinding resin is 80 mgKOH / g, the dispersant is an anionic carboxylic acid ammonium salt dispersant, the carbon black is ordinary pigment tank carbon black, the blackness My value of the carbon black is 300, the oil absorption is 350g / 100g, and the primary particle size is 30nm.

[0082] Preferably, in step Q5, the resin C is one of polyester resin, polyurethane resin and acrylic resin.

[0083] Preferably, in step Q7, the resin D is one of polyester resin, polyurethane resin and acrylic resin.

[0084] Preferably, in step Q4, the solvent is one of a lipid solvent, a benzene solvent, and a ketone solvent.

[0085] Example 3

[0086] A high-brightness black glass bead license plate grade reflective film, which includes, from bottom to top, a transparent composite surface layer 1, a black bead layer 2, a focusing layer 3, an aluminum-plated layer 4, a back adhesive layer 5, and a release layer 6, wherein the release layer 6 is one of release paper, release PET or CPP, the back adhesive layer 5 is a thermoplastic acrylic pressure-sensitive adhesive, the focusing layer 3 is one of polyester resin, polyurethane resin, and acrylic resin, the black bead layer 2 includes a black color layer 21 and glass beads 22, and the glass beads 22 are embedded in the black The color layer 21, the transparent composite surface layer 1 includes a first surface layer 11 and a second surface layer 12, the thickness of the first surface layer 11 is 45μm, the thickness of the second surface layer 12 is 25% of the particle size of the glass beads 22, the sum of the thickness of the black color layer 21 and the second surface layer 12 is 70% of the particle size of the glass beads 22, the second surface layer 12 is a thermoplastic surface layer, the glass beads 22 sink into the second surface layer 12, and the bottom of the glass beads 22 contacts the first surface layer 11.

[0087] As a preference, the method comprises the following steps:

[0088] Q1: Take PET without corona treatment as the coating substrate, the temperature resistance value of the PET is 200°C, the heat shrinkage rate is less than 1.5%, and the thickness is 80μm;

[0089] Q2: Resin A, trimer isocyanate A and methyl cellulose are mixed, wherein the weight ratio of the resin A, trimer isocyanate A and methyl cellulose is 100:8:5.5, and the mixture is stirred for 25 minutes at a speed of 900 rpm. After stirring, the mixture is coated on PET, and then placed in an oven at 115°C and dried for 7 minutes to obtain the first surface layer 11;

[0090] Q3: Mix resin B, chlorovinyl acetate resin and trimer isocyanate B, wherein the weight ratio of resin B, chlorovinyl acetate resin and trimer isocyanate B is 100:12.5:1, stir thoroughly for 25 minutes at a stirring speed of 900 rpm, apply on the first surface layer 11 after stirring, and then place in an oven at 115°C and dry for 7 minutes to obtain the second surface layer 12;

[0091] Q4: Mix black ink and solvent, wherein the black ink contains grinding resin, dispersant, and carbon black, and the weight ratio of the grinding resin, dispersant, carbon black to the solvent is 100:7.5:35:45. Stir thoroughly for 4 minutes, and filter with a 200-mesh mesh to obtain a black pigment.

[0092] Q5: Take resin C, mix it with the black pigment, stir it thoroughly for 7 minutes, then add isocyanate and organotin catalyst, wherein the weight ratio of resin C, black pigment, isocyanate and organotin catalyst is 100:6:8:0.012, continue stirring for 25 minutes, the stirring speed is 900 rpm, after stirring, apply it on the second surface layer 12, and then place it in an oven at 110°C and dry it for 2.5 minutes to obtain an incompletely dried black color layer 21;

[0093] Q6: Using a bead planting device, glass micro beads 22 are evenly and densely arranged on the black color layer 21, and then placed in an oven at 130° C. for drying for 3.5 minutes to obtain a black bead planting layer 2;

[0094] Q7: Take resin D, apply it on the black bead layer 2, and then place it in an oven at 125°C and dry it for 9 minutes to obtain a focusing layer 3;

[0095] Q8: Using vacuum aluminum plating equipment, the vacuum degree is set to 133 Pa, the winding speed is set to 125 m / min, and the aluminum feeding speed is set to 0.25 m / min. After the vacuum aluminum plating is completed, an aluminum plating layer 4 is formed on the surface of the focusing layer 3;

[0096] Q9: Take the release layer 6, apply the thermoplastic acrylic pressure-sensitive adhesive on the release layer 6, and then place it in an oven at 105° C. and dry it for 4 minutes to obtain the back adhesive layer 5;

[0097] Q10: Use a composite device and set the composite pressure to 0.5 MPa to composite the back adhesive layer 5 and the aluminum-plated layer 4, then peel off the PET and the first surface layer 11, and after rolling up, obtain a high-brightness black glass bead license plate grade reflective film.

[0098] Preferably, the glass beads 22 have a particle size of 65 μm and a refractive index of 2.2.

[0099] Preferably, in step Q2, the resin A comprises one or more of thermoplastic polyester resin, polyurethane resin and acrylic resin.

[0100] Preferably, in step Q3, the resin B comprises one or more of a thermoplastic polyester resin, a polyurethane resin, and an acrylic resin, the thermoplastic polyester resin having a glass transition temperature of 40°C, a molecular weight of 20,000 Mw, and a hydroxyl value of 8 mgKOHg, the polyurethane resin having a Shore hardness of 78, a melting point of 125°C, the acrylic resin having a molecular weight of 5,500 Mw, and a glass transition temperature of 68°C, and the chloroacetic acid resin is a ternary chloroacetic acid resin, the chloroacetic acid resin having a vinyl acetate content of 12% and a hydroxyl value of 55 mgKOH / g.

[0101] Preferably, in step Q4, the solid content of the black ink is 35%, the color content is 17.5%, the grinding resin comprises one or more of ternary chloroacetic resin, acrylic resin, polyester resin, and vinyl resin, the hydroxyl value of the grinding resin is 75 mgKOH / g, the dispersant is an anionic carboxylic acid ammonium salt dispersant, the carbon black is ordinary pigment tank carbon black, the blackness My value of the carbon black is 250, the oil absorption is 300g / 100g, and the primary particle size is 25nm.

[0102] Preferably, in step Q5, the resin C is one of polyester resin, polyurethane resin and acrylic resin.

[0103] Preferably, in step Q7, the resin D is one of polyester resin, polyurethane resin and acrylic resin.

[0104] Preferably, in step Q4, the solvent is one of a lipid solvent, a benzene solvent, and a ketone solvent.

[0105] Example 4

[0106] The high-brightness black glass micro-bead license plate grade reflective film obtained in the above embodiments and the existing black 680 model glass micro-bead license plate grade reflective film were taken as comparative examples to test the chromaticity performance, retroreflective performance, breaking strength and breaking elongation performance. The test method is as follows:

[0107] 1. Chromaticity performance test: Test the surface color according to the method specified in GA666-2018;

[0108] Evaluation criteria: LAB measured by a colorimeter represents the chromaticity value of the sample, where the L value represents black and white. The smaller the L value, the darker the sample color.

[0109] 2. Retroreflective performance test: Retroreflective performance tested using the American GM932 retroreflective test instrument;

[0110] Evaluation criteria: 0.2° / 5° is the main angle of retroreflective performance. At this angle, the better the brightness and the higher the value, the better the retroreflective performance of the sample.

[0111] 3. Fracture strength test: Place the sample in an environment of 23℃%±1%, 50%±5% for 12 hours, and then use a universal tensile machine to test the fracture strength performance of the sample;

[0112] Evaluation criteria: In order to meet the stamping performance of the car license plate, the license plate film must meet certain tensile strength properties. According to the requirements of GA666, the tensile strength of the license plate film at 10% tensile strain should be no less than 15N, and the breaking strength should be no less than 25N.

[0113] 4. Elongation at break test: After the sample is placed in an environment of 23℃%±1%, 50%±5% for 12 hours, the fracture strength performance of the sample is tested using a universal tensile machine;

[0114] Evaluation criteria: In order to meet the stamping performance of the car license plate, the license plate film must meet certain tensile properties. According to the requirements of GA666-2018, the tensile strain at break of the license plate film should not be less than 90%.

[0115] The performance parameters of the high-brightness black glass micro-bead license plate grade reflective film obtained in each embodiment of the present invention and the comparative example are shown in Table 1:

[0116] Table 1

[0117] sample Chromaticity performance Retroreflective performance Breaking strength Elongation at break Example 1 L=9.25 0.2 / 5 45 ≥15 / 25 ≥90% Example 2 L=8.30 0.2 / 5 40 ≥15 / 25 ≥90% Example 3 L=9.02 0.2 / 5 43 ≥15 / 25 ≥90% Comparative Example 1 L=10.11 0.2 / 5 30 ≥15 / 25 ≥90%

[0118] In conclusion, the above is only a preferred embodiment of the present invention, and all equivalent changes and modifications made within the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A high-brightness black glass bead license plate grade reflective film, characterized by: The invention comprises, from bottom to top, a transparent composite surface layer (1), a black beading layer (2), a focusing layer (3), an aluminum-plated layer (4), a back adhesive layer (5), and a release layer (6), wherein the release layer (6) is one of release paper, release PET or CPP, the back adhesive layer (5) is a thermoplastic acrylic pressure-sensitive adhesive, the focusing layer (3) is one of polyester resin, polyurethane resin and acrylic resin, the black beading layer (2) comprises a black color layer (21) and glass micro beads (22), the glass micro beads (22) are embedded in the black color layer (21), and the transparent composite surface layer (1) comprises a first surface layer (11) and a second surface layer (12), wherein the thickness of the first surface layer (11) is 35-50 μm, the thickness of the second surface layer (12) is 20-30% of the particle size of the glass beads (22), the sum of the thickness of the black color layer (21) and the second surface layer (12) is 60-80% of the particle size of the glass beads (22), the second surface layer (12) is a thermoplastic surface layer, the glass beads (22) are sunken into the second surface layer (12), and the bottom of the glass beads (22) is in contact with the first surface layer (11).

2. The high-brightness black glass bead license plate grade reflective film according to claim 1, characterized in that: The glass microbeads (22) have a particle size of 45 to 80 μm and a refractive index of 2.1 to 2.

3.

3. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 1, characterized in that: The steps include: Q1: Take PET without corona treatment as the coating substrate, the temperature resistance of the PET is 180-220°C, the heat shrinkage rate is less than 1.5%, and the thickness is 50-100 μm; Q2: Resin A, trimer isocyanate A and methyl cellulose are mixed, wherein the weight ratio of the resin A, trimer isocyanate A and methyl cellulose is 100:0.5-15:3-8, and the mixture is stirred for 20-30 minutes at a speed of 800-1000 rpm. After stirring, the mixture is coated on PET, and then placed in an oven at 75-155° C. and dried for 5-8 minutes to obtain the first surface layer (11); Q3: Mix resin B, vinyl chloride resin and trimer isocyanate B, wherein the weight ratio of resin B, vinyl chloride resin and trimer isocyanate B is 100:10-15:0.5-1.5, stir thoroughly for 20-30 minutes at a stirring speed of 800-1000 rpm, apply the mixture on the first surface layer (11) after stirring, and place in an oven at 75-155°C for drying for 5-8 minutes to obtain the second surface layer (12); Q4: Mix black ink and solvent, wherein the black ink contains grinding resin, dispersant, and carbon black, and the weight ratio of the grinding resin, dispersant, carbon black to the solvent is 100:5-10:30-40:40-50. Stir thoroughly for 3-5 minutes, and filter with 200-mesh cloth after stirring to obtain black pigment; Q5: Take resin C, mix it with the black pigment, stir it thoroughly for 6-8 minutes, then add isocyanate and organotin catalyst, wherein the weight ratio of resin C, black pigment, isocyanate and organotin catalyst is 100:4-8:0.5-15:0.01-0.015, continue stirring for 20-30 minutes, the stirring speed is 800-1000 rpm, after stirring, apply it on the second surface layer (12), and then place it in an oven at 90-130°C and dry it for 2-3 minutes to obtain a partially dried black color layer (21); Q6: Using a bead planting device, the glass microbeads (22) are evenly and densely arranged on the black color layer (21), and then placed in an oven at 110-150° C. for drying for 3-4 minutes to obtain a black bead planting layer (2); Q7: Take resin D, apply it on the black bead layer (2), and then place it in an oven at 100-155°C and dry it for 8-10 minutes to obtain a focusing layer (3); Q8: Using vacuum aluminum plating equipment, setting the vacuum degree to 133 Pa, the winding speed to 100-150 m / min, and the aluminum feeding speed to 0.15-0.35 m / min, after the vacuum aluminum plating is completed, an aluminum plating layer (4) is formed on the surface of the focusing layer (3); Q9: Take the release layer (6), apply the thermoplastic acrylic pressure-sensitive adhesive on the release layer (6), and then place it in an oven at 90-120° C. and dry it for 3-5 minutes to obtain a back adhesive layer (5); Q10: A composite device is used to set the composite pressure to 0.4-0.6 MPa, the adhesive layer (5) and the aluminum-plated layer (4) are composited, and the PET and the first surface layer (11) are peeled off, and a high-brightness black glass microbead license plate grade reflective film is obtained after rolling.

4. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q2, the resin A comprises one or more of thermoplastic polyester resin, polyurethane resin, and acrylic resin.

5. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q3, the resin B comprises one or more of a thermoplastic polyester resin, a polyurethane resin, and an acrylic resin, wherein the thermoplastic polyester resin has a glass transition temperature of 30 to 50°C, a molecular weight of 15,000 to 25,000 Mw, and a hydroxyl value of 6 mgKOHg to 10 mgKOHg, the polyurethane resin has a Shore hardness of 75-80, a melting temperature of 120 to 130°C, the acrylic resin has a molecular weight of 5,000 to 6,000 Mw, and a glass transition temperature of 65 to 70°C, and the chloroacetic acid resin is a ternary chloroacetic acid resin, wherein the chloroacetic acid resin has a vinyl acetate content of 10 to 15%, and a hydroxyl value of 50 mgKOH / g to 60 mgKOH / g.

6. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q4, the solid content of the black ink is 30-40%, the color content is 15-20%, the grinding resin comprises one or more of ternary chloroacetic resin, acrylic resin, polyester resin, and vinyl resin, the hydroxyl value of the grinding resin is 70 mgKOH / g-80 mgKOH / g, the dispersant is an anionic carboxylic acid ammonium salt dispersant, the carbon black is ordinary pigment tank carbon black, the blackness My value of the carbon black is 200-300, the oil absorption is 250 g / 100 g-350 g / 100 g, and the primary particle size is 20 nm-30 nm.

7. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q5, the resin C is one of polyester resin, polyurethane resin and acrylic resin.

8. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q7, the resin D is one of polyester resin, polyurethane resin and acrylic resin.

9. The method for preparing a high-brightness black glass microbead license plate grade reflective film according to claim 3, characterized in that: In step Q4, the solvent is one of a lipid solvent, a benzene solvent, and a ketone solvent.

Citation Information

Patent Citations

  • Reflective film and preparation method thereof

    CN105717566A

  • Retroreflective Sheeting

    US20080226906A1